Incorporating leys in arable systems as a mitigation strategy to reduce soil organic carbon losses during land-use change - Nyameasem, John Kormla; De Los Rios, Josue; Kluß, Christof; Reinsch, Thorsten; Poyda, Arne; Taube, Friedhelm; Loges, Ralf (Frontiers in Environmental Science, 2024)
The intensification of dairy and biogas production in Northwestern Europe has led to the conversion of permanent grasslands to arable land, mainly for silage maize production, resulting in significant soil organic carbon (SOC) losses, highlighting the need for implementing alternative management practices during land use change (LUC) for effective climate change mitigation. This study evaluated the impact of incorporating annual grass-clover leys in three-year arable rotations and slurry application to mitigate SOC losses during LUC. We compared this approach to a continuous silage maize and a permanent grassland on sandy loam soil in Northern Germany. The experiments were simultaneously established at two adjacent 15-year-old sites of permanent grassland and arable cropping, with different levels of initial SOC when the experiment was established. The SOC dynamics in the upper soil layer (0 -30 cm) were evaluated by annual twelve-year sampling (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022). The cropping systems were unfertilized (N0) or fertilized (N1) using cattle slurry at a rate of 240 kg N ha -1 year -1 . The study reveals substantial SOC losses following the conversion of the permanent grassland to grass-clover (ley) based rotation or continuous silage maize, with reductions of 22% and 31%, respectively, compared to baseline levels of the permanent grassland. However, over the 12-year period, the grass-clover ley-based crop rotation demonstrated a 30% reduction in SOC losses compared to continuous silage maize, without compromising dry matter yield. Conversely, the conversion of arable land to grasslands led to SOC increases ranging from 10% to 30%. This recovery was only half the SOC losses observed in the grassland conversion for the same period, indicating a slow-in, fast-out effect during LUC. However, the transition from leycontaining forage rotation to continuous silage maize incurred significant SOC losses of 11%. Overall, these findings underscore the imperative of integrating ley phases to mitigate SOC losses, particularly in high-biomass-yield cropping systems. As a one-year ley phase was insufficient to sustain carbon sequestration in arable crop rotations, extended ley residence times should be considered.